2017
DOI: 10.1016/j.neulet.2017.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Human microglia and astrocytes express cGAS-STING viral sensing components

Abstract: While microglia and astrocytes are known to produce key inflammatory and anti-viral mediators following infection with replicative DNA viruses, the mechanisms by which these cell types perceive such threats are poorly understood. Recently, cyclic GMP-AMP synthase (cGAS) has been identified as an important cytosolic sensor for DNA viruses and retroviruses in peripheral leukocytes. Here we confirm the ability of human microglial and astrocytic cell lines and primary human glia to respond to foreign intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…Consistent with these findings in mice, we have shown that cytosolic administration of a dsDNA ligand can phosphorylate IRF3 and induce IFN-β mRNA expression in primary human microglia and astrocytes (Jeffries and Marriott, 2017), and we have demonstrated that such responses are largely dependent on cGAS expression (Jeffries and Marriott, 2017;Jeffries et al, 2020). Furthermore, we showed that ISG expression is lower in cGAS deficient human microglia both at rest and following infection with HSV-1 (Jeffries et al, 2020).…”
Section: Cgas/stingsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with these findings in mice, we have shown that cytosolic administration of a dsDNA ligand can phosphorylate IRF3 and induce IFN-β mRNA expression in primary human microglia and astrocytes (Jeffries and Marriott, 2017), and we have demonstrated that such responses are largely dependent on cGAS expression (Jeffries and Marriott, 2017;Jeffries et al, 2020). Furthermore, we showed that ISG expression is lower in cGAS deficient human microglia both at rest and following infection with HSV-1 (Jeffries et al, 2020).…”
Section: Cgas/stingsupporting
confidence: 84%
“…Interestingly, while they observed neither constitutive nor IFN-β-inducible expression of cGAS in murine astrocytes, siRNA-mediated cGAS knockdown decreased IFN-β activity in both microglia and astrocytes following exposure to exogenous dsDNA (Cox et al, 2015). Further support for the presence of cGAS in glia has since been provided by our demonstration that primary human microglia and astrocytes both constitutively express cGAS protein and its downstream adaptor molecule STING (Jeffries and Marriott, 2017).…”
Section: Cgas/stingmentioning
confidence: 95%
“…Upon binding dsDNA, cGAS converts ATP and GTP to 2′-5′cGAMP, a cyclic di-nucleotide second messenger, which subsequently binds the ER-membrane bound protein, stimulator of interferon genes (STING), leading to the recruitment of TBK1 and activation of the IRF3-interferon axis (Chen and others 2016). Both cGAS and STING are expressed in human microglia and astrocytes (Jeffries and Marriott 2017), and in vivo studies have begun to establish the importance of cGAS-STING pathway both in CNS infection and in sterile inflammation. For example, cGAS or STING deficient mice are highly susceptible to herpes simplex encephalitis (HSE), abolishing microglial type 1 interferons and the ability of astrocytes to upregulate TLR3 (Reinert and others 2016).…”
Section: Astrocytes As Innate Immune Cellsmentioning
confidence: 99%
“…Similar to other myeloid immune cells such as macrophages, microglia express an array of cell surface, endosomal and cytoplasmic PRRs, allowing them to rapidly respond to the presence of PAMPs and DAMPs in the extracellular milieu and within the cytosol. In addition to the well-studied Toll-like and nucleotide-binding oligomerization domain (NOD)-like families of receptors (TLR and NLR, respectively), more recent work has demonstrated the ability of these sentinel cells to functionally express molecules that serve as cytosolic sensors for foreign and/or damaged nucleic acid motifs that include DNA-dependent activator of interferon-regulatory factors (DAI), retinoic acid-inducible gene (RIG)-like receptors (RLR) and cyclic guanosine monophosphate-adenosine monophosphate synthase (cGAS; Bowman et al, 2003 ; Liu et al, 2010 ; Furr et al, 2011 ; Crill et al, 2015 ; Jeffries and Marriott, 2017 ). Interestingly, non-leukocytic CNS cells, including astrocytes, can also express such innate immune sensing molecules although, in contrast to microglia, such cells appear to constitutively express fewer PRR types and expression levels (Bsibsi et al, 2002 , 2006 ).…”
Section: Introductionmentioning
confidence: 99%